Letters from Alabama : Chiefly Relating to Natural History - Gosse, Philip Henry, 1810-1888 (Book collections on Project MUSE., 2013)
This new and improved edition of Letters from Alabama offers a valuable window into pioneer Alabama and the landscape and life-forms encountered by early settlers of the state. Philip Henry Gosse (1810-1888), a British naturalist, left home at age seventeen and made his way to Alabama in 1838. He was employed by Judge Reuben Saffold and other planters near Pleasant Hill in Dallas County as a teacher for about a dozen of their children, but his principal interest was natural history. Letters from Alabama is a personalized record of Gosse's perceptive observations durin.